Physicochemical Properties of Cassava (Manihot esculenta) Flour (Lafun) Fortified with Bambara Nut (Vigna subterranea) Flour and Sensory Evaluation of Stiff Paste Made from the Blends (Sahel Journal of Life Sciences FUDMA, 2025)
This study investigated the physicochemical properties of cassava flour (lafun) fortified with Bambara nut flour. Cassava tubers and Bambara nut seeds were fermented and processed into flour. The processed flours were formulated into five samples and designated as CAS1 (100:0), CASBAM2 (95:5), CASBAM3 (90:10), CASBAM4 (85:15), and CASBAM5 (80:20) for cassava and Bambara nut, respectively. The functional, proximate, mineral, and vitamin of the flour blends were evaluated using standard methods. The flour blends were used to produce stiff paste and the sensory properties were evaluated using the 9-point hedonic scale. The results showed that there were significant (p